2021
DOI: 10.1155/2021/4411316
|View full text |Cite
|
Sign up to set email alerts
|

Nanonaringenin and Vitamin E Ameliorate Some Behavioral, Biochemical, and Brain Tissue Alterations Induced by Nicotine in Rats

Abstract: Nicotine is the major alkaloid present in cigarettes that induces various biochemical and behavioral changes. Nanonaringenin (NNG) and vitamin E are antioxidants that are reported to mitigate serious impairments caused by some toxins and oxidants. Thus, we aimed to investigate the efficacy of NNG, vitamin E, and their combinations to ameliorate behavioral, biochemical, and histological alterations induced by nicotine in rats. Adult male albino rats were randomly grouped into six equal groups (10 rats/group): c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 129 publications
(149 reference statements)
0
4
0
Order By: Relevance
“… 19 Similarly, a high-energy ball milling technique was used to prepare nano-naringenin, which was characterized with the help of transmission electron microscopy followed by the assessment of pharmacological efficacy of nanosized naringenin in the amelioration of the biochemical, behavioral, and histological changes induced by the nicotine in rats. 20 Another report aimed to formulate the stable nanosized naringenin by the milling methods and exploring its potential applicability for rheumatoid arthritis. Physiochemical properties, physical stabilities, and dissolution functioning of nanosized naringenin were evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 Similarly, a high-energy ball milling technique was used to prepare nano-naringenin, which was characterized with the help of transmission electron microscopy followed by the assessment of pharmacological efficacy of nanosized naringenin in the amelioration of the biochemical, behavioral, and histological changes induced by the nicotine in rats. 20 Another report aimed to formulate the stable nanosized naringenin by the milling methods and exploring its potential applicability for rheumatoid arthritis. Physiochemical properties, physical stabilities, and dissolution functioning of nanosized naringenin were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent past, several studies have reported the ball milling of naringenin for the conversion of naringenin into its nanoparticle forms, and these studies have been added in the Discussion Section. The clinical and therapeutic efficacy of naringenin is restricted due to its lower bioavailability because of the poor solubility. For the enhancement of its solubility, naringenin nanosuspension was prepared by the milling technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoke is a major environmental health threat. The main alkaloid that found in cigarettes is nicotine that responsible for variety of biochemical and behavioral changes 16 . Nicotine induces oxidative stress and testis injury 17 .…”
Section: Discussionmentioning
confidence: 99%